صناعة السياحة ومساهمتها في دعم اهم مؤشرات الاداء الاقتصادي والاجتماعي في الدول النامية- دراسة مقارنة الجزائر-المغرب-مصر 2000-2016 - حدانة, خولة; راضية, بن موسى; نصرات, عمار (جامعة الوادي university eloued, 2017)
تعد السياحة صناعة قائمة بذاتها حيث يساهم العائد من أعمال السياحة مساهمة فعالة في إجمالي الناتج المحلي في الكثير من الدول, وكذلك مساهمتها في دعم أهم مؤشرات الأداء الاقتصادي الداخلي والخارجي كالنمو الاقتصادي ومعدل التضخم ومعدل البطالة واحتياطات الصرف وغيرها من المؤشرات الاقتصادية, وأيضا مؤشرات الأداء الاجتماعي كالدخل الفردي ونصيب الفرد, ونظرا لأهمية هذا القطاع في تنمية اقتصاديات دول شمال إفريقيا, انتهجت كل من الدول المتقدمة أو النامية العديد من الاستراتيجيات للنهوض بقطاعها السياحي من اجل أن تنمي اقتصادها. ونهدف من خلال هذه البحث بالتطرق إلى معرفة السياحة وصناعة السياحة ومساهمتها في قضايا التنمية مع مقارنة الجزائر بالمغرب ومصر من خلال المؤشرات الموضوعة التي ساهمت فيها السياحةTourism is a stand-alone industry where the return en tourism eontributes effectively to the( GDP) Gross domestic product of many countries and contributes to supporting the most important indicators of internal and external performance, inflation rate, unemployment rate, exchange reserves and other economic indicators.as well as indicators of social performance such as indivudial income and per capital incomen.Because of the importance of this sector in the development of the economies of North African countries, both developed and deuelaping countries have pursued many strategies to boost their tourism sector in order to develop their economies.We aim through this research to know the tourism, and tourism industry and their contribution to the devlopment issues while comparing Algeria to Morocco and Egypt through the indicators set in which tourism has contributed
مذكرة ماستر اقتصادي عمومي
Keywords: صناعة السياحة- المؤشرات الاقتصادية- المؤشرات الاجتماعية- اقتصاديات شمال إفريقيا.: Tourism industry- Economic indicators- Social indicators- Economies of North African countries